ANALISA SISTEM DRAINASE JL. MARGO SANTOSO DESA SANGATTA UTARA - ZAN, FAU (KURVA S JURNAL MAHASISWA, 2014)
Subdistrict North Sangatta, especially on Jl. Margosantoso area that is stillflooded by flood inundation maps and the location of the points floodwaters City Sangattaobtained from Dinas Pekerjaan Umum East Kutai.This thesis to analyze the ability ofexisting drainage channels to accommodate surface runoff and stream flow, condition,shape, construction and see the direction of the flow channel in the area of the floodwaters.The problem in terms of this thesis was to analyze the plan rainfall, rainfall intensity ofconcentration, analysis of discharge plan and analysis drainage capacity.The method used is the method of data collection and analysis. First step in thisresearch The collection of primary data and secondary data. Then analyzed by frequencyanalysis method. This method of distribution is analyzed two types Log distribution PersonIII and Gumbel distribution.Value in Raninfall the used to calculate the intensity of rainfall is the rainfalldistribution value Logs Person III period of 10 years. Rainfall intensity used for Mononobeformula, while forthe evaluation of the cross section will be calculated whether thedischarge channel is greater than the discharge plan.The results indicate that the flooding occurred to a drainage system that is notfunction properly. Consequence silting of channels and channel cleanliness very bad nocoherence of all parties involved in protecting and taking care of the cleanliness ofdrainage. And also some channel dimensions are inadequate to accommodate the flooddischarge so we need widening and redesign of drainage network system on MargosantosoNorth Sangatta resulting in a sustainable drainage system.